Experience of an online course on sexuality during pregnancy for residents - Souza Barroso Vieira, Teresa Cristina; Nakamura, Mary Uchiyama; Silva, Ivaldo da; Torloni, Maria Regina; Ribeiro, Meireluci Costa; Scanavino, Marco de Tubino [UNESP]; Souza, Eduardo de (Elsevier B.V., 2017)
Objective: Many obstetrics and gynecology (Ob/Gyn) residents report insufficient knowledge about female sexuality and this has a negative impact on their capacity to manage their patients. The aim of this study was to describe an online course about sexuality during pregnancy for Brazilian Ob/Gyn residents and evaluate their knowledge acquisition. Methods: This longitudinal educational intervention study involved 219 Brazilian Ob/Gyn residents. The online course lasted 24 h (10 video lectures and discussion chats). Upon enrollment, the participants answered a questionnaire in regard to their training, attitudes and practices about sexuality during pregnancy. Participants' knowledge acquisition was assessed using a pre-and post-course test about sexuality during pregnancy. At the end of the course, participants were asked to evaluate their educational experience. Student's t and chi-square tests were used to analyze the pre-and post-course test scores. P values < 0.05 were considered statistically significant. Results: A total of 143 Ob/Gyns (65.3% of those enrolled) completed the course. At baseline, most participants reported that they did not have any sexology classes as undergraduates (62.5%) or in their residency (52.1%), and that they lacked specific knowledge in this area to manage their patients. Mean test scores increased significantly at the end of the course: 4.4 (+/- 1.6) versus 6.0 (+/- 1.3) (out of a maximum score of 10), before and after the course, respectively (p < 0,0001). Most of the residents rated the overall quality of the course as higher than expected. Conclusion: An online course for Ob/Gyn residents was associated with a significant increase in knowledge about sexuality during pregnancy. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Female sexual function; Medical education; Medical residency; Pregnancy; Sexology; Sexuality